Soccer players` sleep quality and training load were affected by the COVID-19 lockdown: an international survey - Romdhani, M.; Washif, J. A.; Taylor, L.; Chamari, K.; on behalf of the "Athletes` Sleep During the Lockdown International Survey" Group Members (International Journal of Sports Physiology and Performance, 2023)
The coronavirus disease 2019 (COVID-19) pandemic and associated lockdowns transiently changed soccer (football) globally. Given that team performance in soccer is multifaceted, it is unsurprising that almost all investigated components were affected by lockdowns. Indeed, government-mandated restrictive measures (eg, quarantine, curfew, or stay-at-home orders; termed simply "lockdown" from here on) compromised (or prevented) access to sporting facilities, resulting in lower loads (volume, frequency, and intensity) and altered modalities of training, often holistically manifesting as insufficient or nonspecific training stimuli. Moreover, lower mood state and emotional intelligence, associated with lower motivation to train, were also reported. Lockdown modified and disrupted lifestyle behaviors (eg, eating, training and sleeping) and external zeitgebers (eg, work schedule, meal timing, sunlight exposure, team training) related to circadian regulation/rhythms of athletes, contributing to lower sleep quality and increased depressive symptoms, which likely affected physical and mental health of athletes during lockdown. Interestingly, recent evidence suggest that some subgroups of athletes (eg, male vs female, elite vs nonelite, younger vs older) were more susceptible to lockdown-mediated effects regarding their sleep and training loads than others. In addition, Ramadan (2020) occurred at the same time as the early 2020 lockdown, which could further disrupt Muslim players` sleep and training behaviors.